Dynamics on Constitutional Court Decision towards Indonesia Citizenship Arrangement: Dinamika Putusan Mahkamah Konstitusi terhadap Pengaturan Kewarganegaraan Indonesia - Bagus Hermanto (Jurnal Konstitusi, 2023)
The 1945 Constitution amendment led into Indonesia state order transition that related also towards state fundamental aspects, including citizenship issue. Discourse has been raises on material and formal context on citizenship arrangement, and develops consideration according to Constitutional Court consent into several Constitutional Court Decisions. This article intention related on dynamics and problematic over citizenship arrangement after Indonesi reform, and Constitutional Court Decision consideration on citizenship issues to evaluate needs to reformulate citizenship arrangement. This article was arranged based on legal research with thesis on arrangement dynamics and Constitutional Court Decision relevance on citizenship supported with statutory laws, conceptual, legal facts, and legal cases approaches. The results reflected citizenship arrangement dynamics related material, formal, legal needs, era and human rights development comprehensively. The Constitutional Court Decision considers Indonesia citizenship into nationalities, maximum protection, full constitutional rights, and comitment to defending single citizenship stelsel into current statutory laws.